ANALISIS PUTUSAN PRAPERADILAN NOMOR: 24/Pid.Prap/2018/PN.Jkt.Sel PENETAPAN TERSANGKA BARU KASUS BANK CENTURY - prasetyo, herlambang ponco (Universitas Negeri Surabaya, 2020)
The South Jakarta District Court dated April 9, 2019 decided on a pretrial case filed by the Anti-Corruption Society Association (MAKI). The pretrial verdict numbered: 24/Pid.Prap/2018/PN.Jkt. The following makes the norm by which the pretrial judge can accept the respondent (Investigator) to determine a suspect for someone who is not involved in the case. The KPK as the respondent was requested by MAKI to be made Budiono, et al as soon as possible to be made a suspect in the Century Bank case. MAKI postulated that because the KPK had indirectly stopped the investigation because within 2 years after Budi Mulya's decision had increased at the cassation level, the KPK did not match the suspect Budiono, et al. Which in the argument of the judge in Budi Mulya's appeal, together with Budiono, et al Involved in the Century Bank case. The purpose of this study is to study the basis of the MAKI and the Judge requesting immediate gathering of Boediono, et al. This research is a normative juridical research study using research proposals, invitations and conceptual. The legal material of this research consists of primary legal material, secondary legal material. The results showed that MAKI argued that the KPK had taken an action to stop the investigation. This is based on that the Criminal Procedure Code is not regulated related to the process of terminating the investigation which must be issued through SP3. Unlike considering the cessation of the prosecution in the Criminal Procedure Code, the prosecution is carried out through the determination of the court. Moreover, the KPK cannot issue SP3 because it has been approved by article 40 of Law Number 30 of 2002 concerning the Corruption Eradication Commission. The basis of judges in making legal breakthroughs is because corruption is an extraordinary crime that must be resolved immediately. Keyword : Pretrial, Decision Number: 24/Pid.Prap/2018/PN.Jkt.Sel, SP3